Efeitos da gravitação sobre a liberdade assintótica em teorias decalibre e violação de Lorentz no modelo padrão - Jean Carlos Coelho Felipe (2014)
The present thesis mostly deals about two problems related to the importance of gravitation in Quantum Field Theory (QFT). These problems have been intensively studied in the last years. First, we investigate the in uence of gravitational e ects on the Quantum Electrodynamics theory (QED), specially analysing the function behaviour before such contributions. This issue is quite interesting since the presence of gravitational sector term in function implies in the asymptotically free behaviour of QED, unlike what occurs in the pure model (without gravitational contributions). Nevertheless, this result has been controversial in literature, being essentially associated on how this problem is operationally treated. From this point of view, we show a way to treat this issue. We show that there is a gravitational contribution for the model although this contribution term has an arbitrary parameter which is regularization dependent. Furthermore, we shown that this contribution is gravitational gauge dependent. In the second problem, through the study of a fermionic model embedded in a curved space time with a Lorentz-violating symmetry term, we shown that is possible to generate a gravitational Chern- Simons-like term (CS-like term). Nevertheless, we will see that term is intrinsecally ambiguous depending on an arbitrary parameter. We will see that the model symmetries are not sucient to x such arbitrariness, leading the CS-like term to be ambiguous and regularization dependent indeed. vi